ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN DI OBYEK WISATA THE SILA’S AGROTOURISM - I NYOMAN GEDE MARTA; I GUSTI AYU META PURMINA DEWI; I MADE HARY KUSMAWAN (Universitas Mahasaraswati K. Mataram, 2023)
The tourism sector has an important role which is shown through the acceptance of state apparatus, regional income revenue, regional development, and being able to increase people's income. The research focus is to analyze the factors that affect income at The Sila's Agrotourism tourism object. The factors that influence income in this case the number of tourist visits, entrance ticket prices and promotion costs are analyzed partially and simultaneously at The Sila's Agrotourism tourism object. To process the resulting data from this study, data analysis was carried out using several methods. The method used is the classical assumption test method, multiple linear regression, multiple coefficient of determination (R2) and statistical tests (t test and F test). The results and discussion of this study are the number of tourist visits that partially have a positive and significant effect on income at The Sila's Agrotourism attractions. Ticket prices have a positive and significant effect on income at The Sila's Agrotourism attractions. Promotional costs have a positive and significant effect on income at The Sila's Agrotourism tourist attraction. The number of tourist visits, entrance ticket prices and promotion costs have a positive and significant effect simultaneously on income at The Sila's Agrotourism tourist attraction.